2016
DOI: 10.1371/journal.pone.0166939
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions, Time Organization and Quality of Life among Adults with Learning Disabilities

Abstract: PurposeThis study compared the executive functions, organization in time and perceived quality of life (QoL) of 55 adults with learning disabilities (LD) with those of 55 matched controls (mean age 30 years). Furthermore, relationships and predictive relationships between these variables among the group with LD were examined.MethodsAll participants completed the Behavioral Rating Inventory of Executive Functions (BRIEF-A), the Time Organization and Participation (TOPS, A-C) and the World Health Organization Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
2
27
1
Order By: Relevance
“…Furthermore, the authors also discussed the role of attention in time judgement, in particular the difficulty for younger children to allocate attentional resources to time, that can explained their poor temporal performances. It should be noted here that time estimation recruited a wide range of cognitive resources, including attentional resources but also other executive resources such as inhibition, switching, and flexibility (Ogden, Wearden, & Montgomery, ; Sharfi & Rosemblum, ). Moreover, recent findings suggested that the attentional and/or executive functions development with age can account for age‐related differences in timing performance (e.g., Baudouin, Isingrini, & Vanneste, ; Hallez & Droit‐Volet, ; Rattat, ).…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the authors also discussed the role of attention in time judgement, in particular the difficulty for younger children to allocate attentional resources to time, that can explained their poor temporal performances. It should be noted here that time estimation recruited a wide range of cognitive resources, including attentional resources but also other executive resources such as inhibition, switching, and flexibility (Ogden, Wearden, & Montgomery, ; Sharfi & Rosemblum, ). Moreover, recent findings suggested that the attentional and/or executive functions development with age can account for age‐related differences in timing performance (e.g., Baudouin, Isingrini, & Vanneste, ; Hallez & Droit‐Volet, ; Rattat, ).…”
Section: Discussionmentioning
confidence: 97%
“…scale shows how student use their organization skills in practice or, in other words, how they order or organize their belongings in the environment (room, desk, etc.) 12,16 .…”
Section: Discussionmentioning
confidence: 99%
“…The procedure was to apply the Behavior Rating Inventory of Executive Function (BRIEF) questionnaire 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These individual-level deficits may also extend the rehearsal time required to automate skills, particularly for complex, multi-step tasks. Finally, the relationship between EF and daily organisation is evident not only in DCD but also in other disorders of learning [35].…”
Section: Recent Experimental Research On Dcd and Its Implications Formentioning
confidence: 96%